Evaluation of Embryo Transfer Pregnancy in Beef Cattle - Ngongo, Elrois; Nurul, Mohamad; Afrila, Akhadiyah (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2025)
Embryo transfer is one of the reproductive biotechnologies that enables rapid and controlled improvement in genetic quality and livestock populations. This technology allows embryos resulting from fertilisation in superior donor cows to be implanted into recipient cows, thereby producing offspring with high genetic potential without reducing the reproductive capacity of the donor cows. This study aims to evaluate the success of embryo transfer (ET) in beef cattle and the factors influencing the birth rate of calves resulting from ET in Lamongan District. Embryo transfer is a promising assisted reproductive technology for accelerating genetic improvement in beef cattle. The research method used in this study is a literature review employing a quantitative descriptive approach. The study was conducted on community-owned embryo transfer farms in Lamongan District over two months, using eight beef cattle as recipients. Data collection methods involved obtaining data from secondary sources related to embryo transfer outcomes at community-owned embryo transfer farms in Lamongan District. The variable in the study was pregnancy rate. The results showed that the pregnancy rate reached 50%, consistent with the general success range for ET (40–70%). All pregnancies were achieved through embryo placement in the upper third of the uterine horn and natural oestrus synchronisation. However, all pregnancies ended in abortion during the second trimester (4–6 months of age). The main identified causes include unverified embryo quality, genetic incompatibility, environmental stress, micronutrient deficiencies, and inadequate post-transfer management. The evaluation showed farmers had varying education and experience, but lacked sufficient technical training.